Designerly ways of knowing : a working inventory of things a designer should know / Danah Abdullah. - Abdullah, Danah (Set margins ;, 2024)
Design thinking has created divisions in the discipline: either designers are too theory driven or simply practitioners. Those feeling lost can easily turn to a language meant to inspire creative production in easy to pitch ways. Led by Antonio Gramsci's advice that knowing thyself requires compiling an inventory, design critic, educator, and researcher Danah Abdulla pays tribute to the late architect, activist, and critic Michael Sorkin, whose original list 'Two Hundred and Fifty Things an Architect Should Know' inspired this updated version targeted at designers. The iterative list is not meant to be a definitive how to guide, but to spark conversations, to prompt critical thinking and to help designers reconfigure their discipline.